Veshch : Mezhdunarodnoe obozrenie sovremennogo iskusstva = Gegenstand : Internationale Rundschau der Kunst der Gegenwart = Objet : Revue internationale de l'art moderne - El Lissitzky; Ehrenburg, Ilja (Berlin : Skythen, 1922)
This trilingual publication Veshch-Gegenstand-Objet was a collaboration between Russian artists El Lissitzky, who designed the striking cover, and Ilya Ehrenburg. Lissitzky had come to Berlin the previous year as representative of new Russian art and culture, and Veshch' begins by celebrating the renewed cultural contacts between Russia and the west after the years of war and revolution. The journal's manifesto goes on to explain that the name (meaning 'object') was chosen because, 'for us, art is nothing other than the creation of new "objects"'. The journal championed Constructivist and Suprematist works but was short lived - only one other issue was published. The Berlin publisher, Skythen Verlag, specialised in Russian publications - Berlin had a population of over half a million Russians in 1923. (bron: http://www.dada-companion.com/journals/per_veshch.php)
Https://monoskop.org/Veshch/Gegenstand/Objet
Online: New York Public Library https://digitalcollections.nypl.org/search/index?utf8=%E2%9C%93&keywords=veshch
Online Blue Mountain: http://bluemountain.princeton.edu/exist/apps/bluemountain/title.html?titleURN=bmtnaam
Russisch
Duits
Frans
Keywords: El Lissitzky; Ehrenburg, Ilja; avant-garde.; Rusland